2008
DOI: 10.14236/ewic/vocs2008.23
|View full text |Cite
|
Sign up to set email alerts
|

Component-Based Description of Programming Languages

Abstract: Research in formal description of programming languages over the past four decades has led to some significant achievements. These include formal syntax and semantics for complete major programming languages, and theoretical foundations for novel features that might be included in future languages. Nevertheless, to give a completely formal, validated description of any significant programming language using the conventional frameworks remains an immense effort, disproportionate to its perceived benefits. Our d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, having to deal with both BAS and action notation was a drawback. Mosses et al [25,43,45,46] reported on subsequent work that led to the present paper.…”
Section: Related Workmentioning
confidence: 63%
“…However, having to deal with both BAS and action notation was a drawback. Mosses et al [25,43,45,46] reported on subsequent work that led to the present paper.…”
Section: Related Workmentioning
confidence: 63%
“…c) Components for Language Specification: PLanCompS funcons are syntactic constructs that ship with their own fixed static and dynamic semantics (presented in MSOS). The PLanCompS specification of a programming language is developed by merely assembling funcons [44]. Example assemblies are larger academic languages [45] and mediumscale ones [46].…”
Section: Related Work A) Lisamentioning
confidence: 99%